ANALYSIS OF QRIS USE ON THE UNITED STATES TRADE WAR POLICY TOWARDS INDONESIA - Atmaja, I Made Dwita (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The issue of trade war tariffs issued by the United States to Indonesia is one of the triggers for the use of the QRIS (Quick Response code Indonesia Standard) payment system which was discussed during trade tariff negotiations between Indonesia and America. America considers the use of QRIS to hinder trade with Indonesia, while according to Indonesia, QRIS makes transactions easier for Indonesian people and countries in Asia that use QRIS. The problem of this research is about the use of QRIS which is a threat to the United States which makes America impose a trade tariff of 32%. Previous research only looked at the trade war between America and China and also the use of QRIS only for UMKM. While this study looks at the use of QRIS which has an impact on the world economy and is still in a trade war situation. The research method used is descriptive qualitative with a literature method through library studies sourced from journals and access to data obtained from websites as information publications. The results of this study user active use of QRIS has the potential to shift the use of ATM cards with the visa or Mastercard logo in the buying and selling transaction process, besides addition to its practical use, the use of QRIS in terms of cost is also quite low. The conclusion of this study is that the use of the QRIS payment system threatens the income from the use of Visa and Mastercard cards, where Visa and Mastercard are payment systems owned by the United States, and the implication of this study is that we should be proud of the QRIS payment system which makes the transaction process easier and cheaper.